2002
DOI: 10.1680/geot.2002.52.9.639
|View full text |Cite
|
Sign up to set email alerts
|

Sidere: numerical prediction of large-strain consolidation

Abstract: Large-strain consolidation theory is widely used for the management of dredged disposal sites. The theory is universally accepted to deal with this problem, though the determination of the material properties is not yet standardised. Decisions made on this level can lead to the prediction of a totally different consolidation history. This paper describes the results of a prediction exercise, performed using a batch of sediment from the river Schelde (Antwerpen, Belgium). Numerical modellers were given the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 12 publications
4
37
0
3
Order By: Relevance
“…For one-dimensional large-strain theory, Gibson et al (1981) used a continuum model to describe the large-strain consolidation of a layer of soil under its own weight. Since Gibson's publication, experimental and numerical issues of one-dimensional large-strain consolidation have been reported (Znidarcic et al, 1984;Tan et al, 1990;De Boer et al, 1996;Sills, 1998;Toorman, 1999;Bartholomeeusen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For one-dimensional large-strain theory, Gibson et al (1981) used a continuum model to describe the large-strain consolidation of a layer of soil under its own weight. Since Gibson's publication, experimental and numerical issues of one-dimensional large-strain consolidation have been reported (Znidarcic et al, 1984;Tan et al, 1990;De Boer et al, 1996;Sills, 1998;Toorman, 1999;Bartholomeeusen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…7. Superimposed on the electrically induced (EK) settlement and the pore water pressure dissipation data are the gravity settlement and pressure dissipation curves reported by Bartholomeeusen and co-workers for similar solids content clay slurry at the same vertical depth [6]. The mass densities of the slurries were 1.65 g/cm 3 , and 1.556 g/cm 3 for the EK and gravity settlements tests, respectively.…”
Section: Resultsmentioning
confidence: 77%
“…Grasso et al (2014) analysed data from a number of previous settling column studies (e.g. Bartholomeeusen et al 2002;Merckelbach and Kranenburg 2004a;te Slaa et al 2013;van and Pham Van Bang 2013) investigating hindered settling of sand-mud mixtures over a wide range of initial concentrations and sand contents. The analysis revealed that sand segregation within the resulting deposits was not always observed and appeared to be prevented at a threshold level of the initial relative mud concentration (e.g.…”
Section: Previous Work On Sand-mud Sedimentationmentioning
confidence: 99%